Quality management and performance in construction industry / Shaferon Wetrom - Wetrom, Shaferon (2020)
Building industry plays a major role in growing country's growth. Building industry development can depend on the quality of its projects. Performance is one of the big tasks that will help businesses excel in their building projects. The increase in the efficiency of building projects in the project's life cycle related to quality control. Although quality management is very critical at the ever step of the project life cycle, quality management at the execution stage would make a major contribution to the final outcome of the construction projects. Throughout the implementation process, the project should concentrate primarily on the significance and factors that influence quality control.